THE IMPORTANCE OF MAINTENANCE PLANNING AND CONTROL (PCM) IN THE PERFORMANCE OF MOBILE EQUIPMENT IN PORT OPERATIONS - Magalhães Viegas Junior, Daniel (Journal of Interdisciplinary Debates, 2024)
Maintenance Planning and Control (PCM) represents one of the most important maintenance departments, as it is responsible for controlling and monitoring the company’s maintenance activities. Collecting and managing data related to maintenance, as well as costs, time, equipment availability index, average time between failures, are part of the scope of PCM management. Ports are responsible for the disposal of products, raw materials, consumer goods, among others. The logistics of these products to the ships is planned and executed with the help of equipment and machinery for handling. It is important that the available equipment available for operations with different types of cargo, be it grains, tanks, containers, others. Thus, the study aims to analyze the maintenance of transport equipment, seeking to present types of maintenance as control tools and indicators. For this reason, a theoretical approach was carried out on the logistics of cargo handling in ports, industrial maintenance, costs and financial and economic viability of the maintenance of which guide the research. The growth scenario needs increased efficiency, availability, ease of transportation combined with reduced expenses, various techniques used in the management of the maintenance sectors, this work proposes a research of the benefits of Maintenance Planning and Control (PCM) for performance of cargo handling equipment in port operations.